IDENTIFICATION OF APRON MARKING STANDARDIZATION ON POTENTIALLY POSING SAFETY RISKS IN AIRCRAFT OPERATION AT AIRPORT - Aulia Pangestuti (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2025)
Based on observations at Adi Soemarmo Airport Boyolali, several apron markings were found to have faded or overlapped, particularly in areas that have undergone layout changes due to terminal development. These conditions reduce the visibility of the markings, potentially posing safety risks in the operation of aircraft and Ground Support Equipment (GSE) vehicles. This study aims to analyze the conformity of apron markings at Adi Soemarmo Airport with the technical provisions stipulated in the Minister of Transportation Regulation No. 21 of 2023. A qualitative descriptive method was applied through direct field observation, photographic documentation, comparison with regulatory specifications, and consultation with Apron Movement Control (AMC) officers to verify operational implications and maintenance practices. The results show that several marking elements, particularly stand boundaries, lead-in/lead-out lines, and equipment parking indications, do not fully meet visibility and standardization criteria as required by regulation, mainly due to color fading and misalignment from overlapping paint layers. These deficiencies reduce the effectiveness of the apron as a navigational aid and may elevate operational risk during peak activity. The novelty of this study lies in employing a regulatory compliance-based assessment specifically referencing PR 21 of 2023, which has not been explicitly adopted in previous apron marking evaluations. The findings contribute both theoretically, by demonstrating apron marking conformity as a measurable safety indicator, and practically, by offering evidence-based recommendations to strengthen AMC supervision and maintenance planning for airside safety enhancement.